1976
DOI: 10.1111/j.1464-410x.1976.tb06686.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Prophylactic Antibiotics in Transurethral Prostatic Resection: a Controlled Trial, with Observations on the Origin of Postoperative Infection

Abstract: Prophylactic antibiotics significantly decrease the incidence of urinary tract infection following endoscopic prostate resection. They are ineffective in reducing the incidence of postoperative fevers, or in reducing the frequency of positive blood cultures during or after operation. A majority of prostate glands harbour colonies of potentially pathogenic organisms, and these are the commonest source of infection of the urinary tract following release by prostatic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(21 citation statements)
references
References 16 publications
1
18
0
2
Order By: Relevance
“…One may assume that tech nical developments in manufacturing endoscopes, refine ment of operation techniques, utilization of inert cathe ters along with closed drainage systems and early removal of urethral catheters must decrease the chance of UTI after T U R -P , yet it is not the case. The most important factor for this unpleasant outcome may be the presence of microorganisms within the prostatic tissue, even though the urine is kept sterile [9,12]. The high rate of infection in the T U R -P group in our study may be due to this factor and other factors like postoperative continuous irrigation and improper handling of the irrigation fluids in unsatis factory containers during the operation.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…One may assume that tech nical developments in manufacturing endoscopes, refine ment of operation techniques, utilization of inert cathe ters along with closed drainage systems and early removal of urethral catheters must decrease the chance of UTI after T U R -P , yet it is not the case. The most important factor for this unpleasant outcome may be the presence of microorganisms within the prostatic tissue, even though the urine is kept sterile [9,12]. The high rate of infection in the T U R -P group in our study may be due to this factor and other factors like postoperative continuous irrigation and improper handling of the irrigation fluids in unsatis factory containers during the operation.…”
Section: Discussionmentioning
confidence: 47%
“…This high rate, in fact, is in contrast to some other clinical investigations which revealed a bacteriuria rate of 10-32% during the operation in patients with ster ile urine preoperatively [6], Some authors assume that uti lization of prophylactic antibiotics in all kinds of endo scopic procedures may decrease the chance of infection and prove to be effective [1,7], Still there is controversy on the subject and those who resist the routine prophy laxis claim that this method raises the possibility o f creat ing resistant species and has no effect on postoperative UTI [2,5], Not only the necessity of prophylactic antibiotic usage but also the antibiotics of choice and the administration schedule are still under debate. There are contradictory reports concerning the same antibiotics -either on behalf or opposing them as prophylactic agents [1,2,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The source of the bacteria responsible for the chills can theoretically be the prostate gland, an ascending route outside of the catheter, the irrigating fluid or the catheter itself during and after transurethral resection of the prostate. 2,5,9 According to most researchers, the prostate gland is the ultimate source of bacteremic episodes and is the origin of urine contamination following transurethral resection of the prostate, [10][11][12] even though the bacteria recovered from the urine and glandular tissue are the same in only 36 to 50% of cases. 12 If it is believed that transurethral resection of the prostate will lead to contamination, broadspectrum antibiotics should be preferred.…”
Section: Discussionmentioning
confidence: 99%
“…General antimicrobial prophylaxis would probably be justified when bacteriaemia and urosepsis were avoided as de noted in some studies [1,2]. However, other investiga tions have shown that these severe complications oc curred both in patients allocated to antibiotic prophylaxis and in the controls [5,9,11], Need of blood transfusions and various catheter prob lems were associated with a significant increase in fever episodes, apparently without a simultaneous increase in urinary tract infections. If this is taken into consideration in clinical decisions, antimicrobial overtreatment may be diminished.…”
Section: Discussionmentioning
confidence: 99%